Investigating the Effect of Formation of Communicative and Pragmatic Competence in Phraseology in Educating Foreign Philological Students - Chernova, Natalia V. (2020)
This article deals with the analysis of the factors influencing the formation of communicative and pragmatic competence in the process of teaching foreign students of the Faculty of Philology, Department of Russian Phraseology. The authors prove that the system of training future teachers of Russian has no sections and courses aimed at the formation of communicative and pragmatic competence in Russian phraseology. The study of the assimilation of phraseological units was carried out in several stages. The first is related to the definition of the level of knowledge of the phraseological system of the Russian language. The second is the level of understanding of certain phraseological units by philology students. The third is the ability to express an evaluative attitude towards someone using phraseological units. The fourth is related to the ability to use phraseological units when evaluating something, any event, phenomena.